Assessment of particulate matter concentrations and air quality index during road construction-related activities in Ghana - Isaac Kofi Yankson; Samuel Okyere; Fred Wireko-Manu; Emmanuel Dugan; Akua Fosua Ampomah; Emmanuel Acquah; Ebenezer Yeboah-Adjei; Paul Okyere; Akua Koaso Yalley; Daniel Asenso-Gyambibi; Peter Donkor; Charles Mock; et al. (Discover Environment)
Abstract Road construction involves activities that emit pollutants, including particulate matter, which harms humans. This study determined and compared particulate matter (PM1.0, PM2.5 and PM10) levels and air quality index (AQI) at unpaved roads, asphalt overlay, chip-sealed and asphalt-producing sites in Ghana and the health risks posed by their exposure. It was conducted in the Ashanti and Ahafo Regions, Ghana and was cross-sectional using the low-cost sensor, PCE-RCM16. Data collection took place, January-May, 2020. The asphalt-producing, asphalt overlay, chip-sealed and unpaved road sites had mean PM10 concentrations of 12.7-fold, 7.4-fold, 6.1-fold and 2.6-fold respectively of the 2021 World Health Organisation (WHO) air quality guideline (AQG) daily limit, 45 μg m−3. The mean PM2.5 concentrations were 30.4-fold, 17.2-fold, 14.1-fold and 6.1-fold greater than the daily AQG limit, 15 μg m−3 respectively. The mean PM1.0 values were of grave concern. Using the AQI, the asphalt-producing and asphalt overlay sites were considered “hazardous”, chip-sealed site was “very unhealthy” and the unpaved sites were “unhealthy for sensitive groups”. Type of activity influenced pollution levels (p < 0.01). All the sites were polluted above the WHO limits. Authorities should ensure the wearing of personal protective equipment, strict adherence to the WHO AQG and apply appropriate sanctions to offending firms/workers.